Collective Teacher Efficacy: A Critical Review of Education’s Top Influence - Hoogsteen, T.J. (Advances in Social Sciences Research Journal, 2020)
Statements claiming that efforts of policy makers, system and school leaders, and staff developments toward education reforms might be better served by strategically and intentionally considering how to foster collective efficacy throughout the conceptualization, design, delivery, and assessment of change initiatives (Donohoo, 2018, p. 340) require continued attempts to provide critical reviews of the available literature, as does this review. Furthermore, Donohoo (2018) discussed the need for reviews of research to examine what is known about the causal directions amongst the outcomes of collective efficacy, and the current article does this as well. This is especially important and timely considering that collective teacher efficacy (CTE) is regarded by many as the top influence on student achievement. This review undertakes an examination of articles related to CTE and achievement, leadership, teacher outcomes, and professional learning communities. It draws attention to important future directions for collective efficacy research as well as valuable insights for school and district leaders responsible for determining school and system priorities.